Makna Lirik Dan Nilai Budaya Pada Lagu Tradisional Jepang Momiji - Rahma Fitri Alifah (KIRYOKU, 2020)
Japan has four distinct seasons each year, called Haru (spring), Natsu (summer), Aki (fall), and Fuyu (winter). Each season has a different natural state, has a different color, and a different atmosphere. For example, in autumn (aki), many leaves turn yellow or red, so this is a characteristic of autumn. This distinctive characteristic is embodied in a song entitled "Momiji". This study aims to analyze the meaning of the Momiji song lyrics and the hermeneutic reading of the Momiji song lyrics. Momiji song lyric data is taken from http://www.worldfolksong.com. This study uses an interpretive qualitative method. This research concludes that the cultural meaning that appears in these lyrics can be seen in the words "Susumoyou and Nishiki". Susumoyou is a pattern found on a kimono that has a plain top, so the pattern is seen as beautiful. Nishiki is silk fabrics that are woven beautifully using colorful threads.